2012
DOI: 10.3928/00989134-20120509-03
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Malnutrition Screening Tool for Older Adults at High Risk of Hospital Readmission

Abstract: Malnutrition is a serious problem in older adults, particularly for those at risk of hospital readmission. The essential step in managing malnutrition is early identification using a valid nutrition screening tool. The purpose of this study was to validate the Malnutrition Screening Tool (MST) in older adults at high risk of hospital readmission. Two RNs administered the MST to identify malnutrition risk and compared it with the comprehensive Subjective Global Assessment (SGA) to assess nutritional status for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
3
29
0
1
Order By: Relevance
“…Given changes in nutritional status, the differences between the various indicators used for nutritional diagnosis (3,6,9,16,17,21,24) , and the peculiarities of older adults, new studies are needed on the nutritional status of hospitalized older surgical patients, and on continuous and routine nutritional status monitoring. The TLC of patients at nutritional risk also differed significantly from the TLC of patients not at nutritional risk according to the NRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given changes in nutritional status, the differences between the various indicators used for nutritional diagnosis (3,6,9,16,17,21,24) , and the peculiarities of older adults, new studies are needed on the nutritional status of hospitalized older surgical patients, and on continuous and routine nutritional status monitoring. The TLC of patients at nutritional risk also differed significantly from the TLC of patients not at nutritional risk according to the NRS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of nutritional screening instruments (24) is critical given the prevalence of malnutrition and/or nutritional risk in hospitalized older adults (8,24) . In a recent prospective study, Calvo et al, 2012, found that 77% of hospitalized older adults were at risk of malnutrition or malnourished according to the mini-nutritional assessment, and that low serum albumin, cholesterol, and vitamins A and D were associated with malnutrition or risk of malnutrition (3) .…”
Section: Introductionmentioning
confidence: 99%
“…6,9 Older adults are particularly vulnerable to undernutrition or specific nutrient deficiencies because they often have diseases and disabilities that limit dietary intake. 3,[10][11][12] Malnutrition has negative impacts on patients and the health care system, leading to more complications, slowed recovery, and higher costs of care. Study results show that malnourished hospital patients, compared with their adequately nourished peers, are more likely to experience pressure ulcers, 13 postsurgical infections, 14,15 and falls 16 and are at greater risk for death.…”
mentioning
confidence: 99%
“…Risk of malnutrition was identified using the MST, which has been shown to have good sensitivity and specificity in the acute geriatric population14 21 and the ED 15. The MST was newly incorporated into the ED admission process for the purposes of the study.…”
Section: Methodsmentioning
confidence: 99%